Preparation of objectives and outcomes for engineering education - Hossen Memarian (آموزش مهندسی ایران, 2011)
One of the prerequisites of successful education is establishment of suitable objectives for courses and educational programs. Having the course objectives, instructors can design their course content and teaching method aptly; and students can focus more on those sections that they really need to learn. At the end of an educational process, both the instructors and the universities are interested to assess the knowledge, skills, and attitudes that were transferred to the students throughout the course or program. Learning objectives and outcomes reveal what students have gained after completing a course or program respectively. Success of an instructed education can be measured by internal and external assessment. Internal assessment is carried out within each educational institution; while external assessment is undertaken by independent centers, such as Engineering Education Accreditation Organization of Iran. According to a paradigm that is followed in many countries, fulfillment of eight general criteria and one specific criterion is required for accreditation of an engineering program. Between those criteria, criterion 2 involves objectives, while criterion 3 deals with outcomes. Considering the prime significance of these two criteria in the accreditation process, this paper discusses a practical method for preparing learning objectives for courses; as well as outcomes that measure the success of an educational program. The method presented in this paper is suggested as a standard for internal assessment of objectives and outcomes as well as external assessment of programs to be carried out by the Engineering Education Accreditation Organization of Iran.